2002
DOI: 10.1034/j.1600-0463.2002.1101005.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric inverted hyperplastic polyp. Report of four cases and relation to gastritis cystica profunda

Abstract: Gastric inverted hyperplastic polyp (IHP) is a rare type of gastric polyp, and is characterized by downward growth of the hyperplastic mucosal components into the submucosa. To the best ofour knowledge, 16 gastric IHP cases have been described in the English literature, but the pathogenesis has not been established. We report the clinical and pathological findings of four gastric IHP cases. The lesions were mainly composed of hyperplastic foveolar-type glands with focal cystic dilatation. Pyloric type glands, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 14 publications
3
37
0
Order By: Relevance
“…These data confirm the chronological changes in the hypertrophic mucosa on top of the SMT. No report has confirmed the milky white mucous and calcification structures exuding from the biopsy site directly and confirmed indirectly during the ESD [14] . Although GHPs are benign tumors, approximately 20% coexist with paracancerous or cancerous areas [15] ; therefore, it is important to diagnosis these polyps, and the recommended treatment is an en bloc resection using an ESD method.…”
Section: Discussionmentioning
confidence: 99%
“…These data confirm the chronological changes in the hypertrophic mucosa on top of the SMT. No report has confirmed the milky white mucous and calcification structures exuding from the biopsy site directly and confirmed indirectly during the ESD [14] . Although GHPs are benign tumors, approximately 20% coexist with paracancerous or cancerous areas [15] ; therefore, it is important to diagnosis these polyps, and the recommended treatment is an en bloc resection using an ESD method.…”
Section: Discussionmentioning
confidence: 99%
“…However, they may occasionally manifest as an anemia secondary to chronic blood loss or as an intestinal obstruction. It is noteworthy that gastric hamartomatous polyps are benign disease pathologically but about 20% of gastric hamartomatous polyps coexisted with gastric adenocarcinoma (6). Therefore, the diagnosis and treatment of these polyps remain important problems.…”
Section: F I G U R E 3 a : Mi C R O S C O P Y O F T H E E N D O S Cmentioning
confidence: 99%
“…Therefore, the diagnosis and treatment of these polyps remain important problems. Previous papers described that it is difficult to make diagnosis before treatment (6) (9). And, many reports revealed that if the lesion is 10 mm or greater, ESD method has been selected to prevent piece-meal resection, which is liable to provide insufficient tissue for accurate pathologic diagnosis (10,11).…”
Section: F I G U R E 3 a : Mi C R O S C O P Y O F T H E E N D O S Cmentioning
confidence: 99%
“…GCP is a rare gastric lesion characterized by the presence of gastric glands in the submucosa of the stomach with normal overlying mucosa and is often mistaken for other more common gastric pathologies [3][4][5][6][7][8]. An unspecified mucosal insult or injury is widely accepted as the nidus for GCP genesis, however, the pathophysiology is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was not until 1981 that Franzin and Novelli coined the term "gastritis cystica profunda," and described fifteen cases of GCP that were initially confused with other gastric pathologies, such as mature erosions and gastric adenomas [2]. Since that time, very few additional cases of GCP have been reported, and in these instances GCP was initially thought to represent Ménétrier's disease, [3][4][5] gastric adenocarcinoma, [6,7] inverted hyperplastic polyps, [8] and other pathologies. This report describes a rare case of a GCP in the antrum of a surgery-naïve 39 year-old female which endoscopically and sonographically was consistent with a gastrointestinal stromal tumor (GIST).…”
Section: Introductionmentioning
confidence: 99%